Keuntungan Usahatani Kubis Di Desa Batur Tengah, Kecamatan Kintamani, Kabupaten Bangli - Sofiani Ritani; I Ketut Arnawa; Made Tamba (Fakultas Pertanian dan Bisnis Universitas Mahasaraswati Denpasar, 2021)
The development of cabbage farming in Batur Tengah Village, namely production and prices tent to increase so that the purpose of this study is to analyze the costs and revenues of cabbage farming in Batur Tengah Village, Kintamani District, Bangli Regency and to analyze the profit level of cabbage farming in Batur Tengah Village, Kintamani District, Bangli Regency. this research was conducted in Batur Tengah Village, Kintamani District, Bangli Regency, from march 2021 to july 2021. Datan analysis withR/C ratio. the determination of farmer respondents used a random sampling method. the population in this study were all farmers who did cabbage farming in Batur Tengah Village, Kintamani District, Bangli Regency, amounting to 110 farmers. samples were taken as many as 32 farmers. the results of this study indicate that the production cost per season of cabbage farming in Batur Tengah Village is Rp. 7,165,735.00 per land area of ​​9.5 acres, with farming revenues of 11,412,000.00 per land area of ​​9.5 acres. the profit of cabbage farming in Batur Tengah Village per season is Rp. 4,246,265.00 per land area of ​​9.5 acres, with an R/C of 1.59. research on the benefits of cabbage farming needs to be continued to see the obstacles and supports for the development of cabbage farming in the future